2007
DOI: 10.1016/j.oraloncology.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of connexin 43 in nasopharyngeal carcinoma cells is related to promoter methylation

Abstract: Summary Down-regulation of Cx43 expression had been shown to occur in nasopharyngeal carcinoma cells. The present study was undertaken to estimate if methylation of the promoter region in Cx43 gene was responsible for the repression of Cx43 expression in the CNE-1 nasopharyngeal carcinoma cells. Calcein transfer and lucifer yellow transfer were detected to evaluate gap junction intercellular communication (GJIC) in CNE-1 cells. It was found that the control CNE-1 cells showed no fluorescent dye transfer. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…To further support the notion that huMETCAM/MUC18 was expressed at a low level in NPC tissues, we showed that low levels of huMETCAM/ MUC18 were also expressed in seven established NPC cell lines in comparison with that in a human malignant melanoma cell line, SK-Mel-28, two metastatic human prostate cancer cell lines, DU145 and PC-3, and a human bladder cancer cell line, TSU-Pr1. Taken together, we concluded that the diminishing or the loss of huMETCAM/ MUC18 expression may be a new potential biomarker for emergence of NPC, whereas the re-gain of its expression may be a new potential biomarker for the progression of NPC to malignant stages, in addition to other potential markers for this cancer, such as the loss of E-cadherin and connexin 43 expression (Huang et al, 2001;Li et al, 2004;Yi et al, 2006), the gain of ICAM expression (Yu et al, 2004), and the presence of EBV-specific LMP1 (Tsai et al, 2002;Yoshizaki, 2002).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…To further support the notion that huMETCAM/MUC18 was expressed at a low level in NPC tissues, we showed that low levels of huMETCAM/ MUC18 were also expressed in seven established NPC cell lines in comparison with that in a human malignant melanoma cell line, SK-Mel-28, two metastatic human prostate cancer cell lines, DU145 and PC-3, and a human bladder cancer cell line, TSU-Pr1. Taken together, we concluded that the diminishing or the loss of huMETCAM/ MUC18 expression may be a new potential biomarker for emergence of NPC, whereas the re-gain of its expression may be a new potential biomarker for the progression of NPC to malignant stages, in addition to other potential markers for this cancer, such as the loss of E-cadherin and connexin 43 expression (Huang et al, 2001;Li et al, 2004;Yi et al, 2006), the gain of ICAM expression (Yu et al, 2004), and the presence of EBV-specific LMP1 (Tsai et al, 2002;Yoshizaki, 2002).…”
Section: Discussionmentioning
confidence: 73%
“…The evidence of association of SNPs with cancer metastasis in many cancer types has also begun to emerge (Craefor ad Hunter, 2006). The LMP1 gene of EBV has been shown to down regulate the E-cadherin expression via the activation of DNA methytransferases (Tsai et al, 2002;Krishna et al, 2005) and also promoter methylation down-regulates the expression of connexin 43 in NPC (Yi et al, 2006). The fine mapping in the chromosome11q22-23 region, in which the huMETCAM/MUC18 gene resides, indicates that hyper-methylation of the region may abolish the DOI:http://dx.doi.org/10.7314/APJCP.2014.15.1.245 Human METCAM/MUC18 Changes in Nasopharyngeal Carcinomas and Metastatic Lesions expression of the gene and is associated with the NPC development during the progression of NPC (Lung et al, 2004;Lung et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that various epigenetic factors are responsible for the down regulation of Cx43 during cell transformation (Yi et al, 2007). Our unpublished data indicates that certain oncogenic microRNAs (miRNAs) may be important players in down regulating the tumor suppressive Cx43 protein in colon tissue.…”
Section: Discussionmentioning
confidence: 80%
“…Hence, study of the formation of gap junctions could suggest the adaptability of cells that are transplanted into the heart infarct [28,31]. Commonly used methods for gap junction imaging and quantification are fluorophore transfer and immunostaining [2,23,39]. Live cell gap junction imaging has been reported which involved tagging the connexins with GFP [7].…”
Section: Introductionmentioning
confidence: 99%